AQUAPYROLYSIS OF ORGANIC MATTER FROM THE RIPHEAN CARBON-RICH ARGILLITE OF THE YURUBCHEN-TAKHOM OIL AND GAS ACCUMULATION ZONE - Larichev A.I.; Melenevskii V.N.; Shvedenkov G.Yu.; Sukhoruehko V.I. (My University, 2004)
Evident from the presented results, Riphean sedimentary rocks similar to the experimental ones may generate, in the course of natural OM maturation, approximately 40 kg/t of liquid and 50 kg/t of gaseous hydrocarbons (maximal estimate). Thus, our experimental results confirm the following fact. In terms of oil-generating potential, ancient organic matter is not inferior to its younger counterparts, including the well-known Bazhenov Formation, which is the main oil-generating formation in the West Siberian oil- and gas-bearing province. These results testify to a high oil-generating potential of Riphean sequences in the Yurubchen-Takhom oil and gas accumulation zone (Baikit oil- and gas-bearing region, Siberian Platform).
Keywords: Riphean; Precambrian::Proterozoic::Riphean; Докембрий::Протерозой::Рифей